Phenotypic, genetic and environmental trends of production traits in Phule Triveni synthetic cow - AMBHORE, G S; SINGH, AVTAR; DEOKAR, D K; SINGH, MANVENDRA; SAHOO, S K (The Indian Journal of Animal Sciences, 2017)
The research data spread over a period of 37 years (1976 to 2012) were utilized to study the production traits, viz. first lactation 300 day milk yield (FL300DMY), first lactation total milk yields (FLTMY), first lactation length (FLL) and first dry period (FDP). The 493 first lactation performance records of Phule Triveni cows reared at Research Cum Development Project on Cattle, Mahatma Phule Krishi Vidyapeeth (MPKV), Rahuri was used to investigate the effect of environmental factors on first lactation production traits. Phenotypic, genetic and environmental trends were estimated using Smith II (SM-II) and best linear unbiased prediction (BLUP) methods in these traits. The estimated annual phenotypic, genetic and environmental trends were -20.70 ± 1.42 kg, 33.38 ± 48.99 kg (SM-II) and 1.31 ± 0.60 kg (BLUP) and - 54.08 ± 49.01kg (SM-II) and -22.01 ± 1.58 kg (BLUP) for FL300DMY, - 21.01 ± 4.18, 21.35 ± 60.09 kg (SM-II) and 2.15 ± 0.73 kg (BLUP) and - 42.36 ± 60.23 kg(SM-II) and - 23.16 ± 4.24 kg(BLUP) for FLTMY, - 0.44 ± 0.30 days, 4.27 ± 4.94(SM-II) and 0.09 ± 0.13(BLUP) days for FLL, 0.98 ± 0.24 days, - 0.99 ± 3.58(SM-II) and - 0.11 ± 0.08 (BLUP) days, 1.97 ± 3.59 (SM-II) and 1.09 ± 0.25(BLUP) days for FDP, respectively. The genetic trends for most of the production traits were positive except FDP revealing desirable improvement in performance traits over time.